The Effect of Nutritional Education with Leaflet and Diet Application on Nutritional Status Changes in Obese College Students (Unnes Journal of Public Health, 2021)
Obesity is excessive body fat condition due to differences in energy consumption and expenditure. In Indonesia, the prevalence of obese women >18 years old is 32.9%. Interventions are performed with control eating and increased physical activity through an educational approach. A Leaflet is a print media containing some information, while my weight loss diet application is used by people that want to lose weight. Therefore, this study aims to determine the effect of nutritional education with leaflet and my weight loss diet application on nutritional status changes in obesity. True experimental design was used with pre-post test on female students divided into two groups in Universitas Brawijaya (n= 44) and selected by purposive sampling. Also, Independent-Samples T-Test and Mann Whitney analysis were conducted. The results showed a body mass index decrease in both media and no significant change related to BMI (p = 0.733). However, the decrease was more shown on the leaflet, where the body fat percentage had a significant change (p = 0.000). Hence, intervention using the leaflet is more effective on nutritional status changes related with BMI and body fat percentage in obese students.